Sublingual Immunotherapy Decreased the Serum Levels of Interleukin-36γ in Allergic Rhinitis - Xiaowei Qin; Chunrui Wang; Jueqi Li; Xiaopeng Zhang; Tianhong Zhang (Mediators of Inflammation)
Conclusion: The changes of IL-36γ during SLIT were related to the inhibited function of ILC2, implying that IL-36γ may be used as a new biomarker for monitoring the efficacy of SLIT in AR.